THE VAGUENESS OF KH. MUHAMMAD LUTHFI GHOZALI’S THOUGHTS ON LADUNI SCIENCE - Fatoni, Muhamad; Suminto, Suminto; Baba Kurnia, Muhammad; Zahrok, Kharismatus; Sari, Isma Yunia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This article discusses KH. Muhammad Luthfi Ghozali’s thoughts on laduni science, that it can be gained by anyone who has valid reason. Generally, Muslim intellectuals such as al-Ghazâlî and Suhrawardî believe that laduni is given specially for saints. This is qualitative-library research since the primary data are from “Mencari Jati Diri Volume 2” book. Authors employed content and critical analysis. The study shows that Luthfi Ghozali’s laduni science epistemology is vague. First, his concept that laduni is laddunîyah rabbânîyah science which is primarily about legacy. Those who want the knowledge must establish a spiritual relationship in the form of tawassul. On the other hand, legacy should be given effortlessly. The second vagueness is on the knowledge journey theory. He stated, both ways (of gaining knowledge) begin from senses; while in his definition, laduni directly gets into one’s soul. The last is about the causes of acquisition. The second cause explained that piety is a result of riyâdhâh, mujâhadah, and dzikr-those three should be the real causes of laduni. The third cause, nubuwah and walâyah, is defined inconsistently. On one hand, it is meant for the prophets and saints. On the other hand, he defines it as closeness.",